Boyle on Atheism - MacIntosh, J. J. (Toronto Studies in Philosophy, 2005)
Opposition to atheism flourished in the seventeenth century, and famed scientist-philosopher Robert Boyle (1627–91) was so opposed to it that he had planned throughout his life to publish a work on his various objections, a project that never came to fruition. Despite this, a great deal of his thought on atheism still exists within the manuscripts he left behind after his death.With Boyle on Atheism, J.J. MacIntosh has culled the Boyle manuscripts held at the Royal Society Library in London and transcribed the portions that relate to atheism, arranging them in the order Boyle appears to have intended (as outlined in one of the pieces). The volume contains Boyle's views on the causes (and remedies) of atheism, the nature of God, various possible arguments for God's existence, the excellency of Christianity, and the character of atheists and the deficiencies to be found in their arguments.To round out the volume, MacIntosh has added a short biography of Boyle, a general introduction to the text, introductions to the various sections, and explanatory footnotes. Boyle on Atheism provides, for the first time, and at length, publication of the material that Boyle himself thought worth marshalling on a subject of great personal importance.